1989
DOI: 10.1161/01.res.65.5.1182
|View full text |Cite
|
Sign up to set email alerts
|

Capillary growth in anemia-induced ventricular wall remodeling in the rat heart.

Abstract: To determine whether anemia-induced cardiac hypertrophy affects ventricular size and shape and the component structures of the capillary network of the left and right ventricles, young male rats were fed an iron- and copper-deficient diet for 7 weeks. By that time, blood hemoglobin content fell to 5 +/- 1 g/dl, and packed cell volume fell to 18 +/- 3%. To further characterize the implications of anemia, red blood cell number, hemoglobin corpuscular content, systemic arterial pressure, heart rate, and blood vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 40 publications
7
30
0
2
Order By: Relevance
“…IDA induces LV eccentric hypertrophy in developing rats (16,21,22,27); however, the molecular mechanism responsible for LV remodeling in this setting has been unknown. Recent studies showed that Epo treatment improves quality-of-life scores and LV ejection fraction in patients with HF (14), indicating that Epo has protective effects on cardiac diseases.…”
Section: Possible Role Of Serum Epo and Cardiac Stat3 Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…IDA induces LV eccentric hypertrophy in developing rats (16,21,22,27); however, the molecular mechanism responsible for LV remodeling in this setting has been unknown. Recent studies showed that Epo treatment improves quality-of-life scores and LV ejection fraction in patients with HF (14), indicating that Epo has protective effects on cardiac diseases.…”
Section: Possible Role Of Serum Epo and Cardiac Stat3 Phosphorylationmentioning
confidence: 99%
“…Thus iron deficiency anemia (IDA) is obviously important not only as a primary cause, but also as a facilitator, of HF. Numerous studies have shown that IDA leads to left ventricular (LV) hypertrophy in developing rats (16,21,22,27), but no data about its molecular mechanisms, including the molecular signaling pathways, of IDAinduced cardiac remodeling, are available.…”
mentioning
confidence: 99%
“…The positively stained (red) fibrotic area was expressed as a percentage of total area. Total cardiac myocyte numbers were estimated using a published method (19). Briefly, the number of nuclei per unit area of myocardium (N(n) A ) was determined in 20 fields (40ϫ).…”
Section: Gsk-3␣mentioning
confidence: 99%
“…[23][24][25] VEGF-knockout mice developed ischemic cardiomyopathy because of limited capillary density. 24 Patients with dilated cardiomyopathy and decreased capillary density show decreased VEGF expression.…”
Section: Impaired Coronary Angiogenesis During Inhibition Of No Synthasementioning
confidence: 99%